ANALISIS PEMODELAN 3 DIMENSI BANGUNAN BERSEJARAH MENGGUNAKAN FOTOGRAMETRI JARAK DEKAT (STUDI KASUS: MAUSOLEUM DINGER, JAWA TIMUR) - Falahesa, Dean Ahmed; Cahyono, Agung Budi; Hidayat, Husnul (Geoid, 2019)
The Dinger Mausoleum is a tomb with a Dutch architectural style that was used to store the body of a Dutch national named Jan Dinger and has been designated as a cultural heritage building by the Batu City Government. This tomb with its status as a cultural heritage must be tried to preserve and preserve its original form in accordance with Law No. 11 of 2010 concerning Cultural Heritage. In this study, conservation efforts were carried out by documenting the tomb in the form of a 3D reconstruction model. Documentation activities are carried out by acquiring data and creating 3D models from Dinger Mausoleums both from the outside (exterior) and from inside (interior) considering that the tomb is in the form of a building which means it has space inside, using close-range photogrammetric methods. The 3D model that has been formed is then analyzed for the level of accuracy of the data acquisition and tomb modeling process. An analysis of the level of suitability in the 4th order class (LoD4) is also carried out because 3D modeling includes the interior of the tomb building. The results of the data acquisition took the form of exterior photos and photos of the interior of the Dinger Mausoleum, and the results of the analysis of the RMSE values were less than 0.2 m, thus fulfilling the Level of Detail 4 criteria (LOD 4).